Remote results of treatment of patients with Monteggia injuries by transosseous osteosynthesis - I. N. Mikhaylov; M. E. Puseva (Acta Biomedica Scientifica, 2013)
The research is based on the analysis of treatment of 30 patients (during 2002-2010 years) with. Monteggia injuries by transosseous osteosynthesis. The aim. of the work was to show opportunities of transosseous osteosynthesis as mini-invasive method that allows to restore anatomical structures of injured segment by closed method. Separate fixation of radial and ulnar bones used in the work allowed to remove fixator from the radial bone without losing rigidity of fixation of ulnar bone and. to provide the opportunity of earlier development of rotation. At the estimation of effectiveness of treatment we considered functional activity of injured upper extremity in addition to the result of clinical and. radiologic examination of the patient. The accent was made on the typical mistakes at the treatment of these patients. Study of outcomes of treatment showed that 13 patients (86,6 %) had. usual degree of social integration in 6 months, 2 patients (13,4 %) had. slight limitations of social life. In a year all patients were considered socially integrated.